Macronutrients (NPK) balance in rice field and dryland maize cropping systems - Sugeng Winarso; Rendy Anggriawan; IGM Subiksa; Rakhmaghfiroh Geonina Ganestri; Salsabila Regina Intansari; Dedik Budianta (Journal of Degraded and Mining Lands Management, 2022)
Fertilisers, especially those containing NPK nutrients, have become a necessity in farming both rice fields and dry land. Most of the application of fertilisers is based on plant commodities and less based on the nature of the diversity of the soil or growing media. This study aimed to determine the balance of NPK nutrients and the nutrient elements that became the limiting factor in the rice and dryland maize cropping systems. The study was conducted at a rice field in Jember District and on dry land in Bogor District with maize plants. The fertiliser used is organic fertiliser. Nutrient balance is obtained by calculating the difference between the total input of nutrients N, P, and K given and the total output of nutrients N, P, and K transported by plants. The results showed that the combination of fertilizing treatment with biochar (50%), fish waste (25%), and chicken manure (25%) up to 10 t/ha on rice field soil at the experimental location in Jember had to limit factors for plant growth: low organic matter content, trace elements essential nutrients N and P are also low. Likewise, the combination of inorganic NPK fertiliser treatment with organic fertiliser up to 600 kg/ha on dry land in Bogor has not been able to improve its fertility status with limiting factors: low organic matter content, low N-total, and low exchangeable K.